Feeding Management on the Performance of Meat Duck at the Starter Period - Sabrina, Sabrina; Arlina, Firda; Nova, Tertia Delia; Siddiq, Hifzhil; Jannah, Ayu Nur (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
The objective of this research was to study the effect of restricted feeding period and refeeding on muscovy duck performance in the starter period. This study used 100 male day-old duck of Muscovy ducks that were kept for 1 day to 9 weeks of age. This study used a Randomized Block Design (RBD) with 5 treatments and 4 replications. The ratio given was 30% of the normal ratio. The treatment of restricted feeding period were ad libitum (A), 1 week (B) 2 weeks (C) 3 weeks (D) and 4 weeks (E) The variables observed were feed consumption, body weight gain, feed conversion (FCR) protein intake, growth rate, carcass and carcass percentage. The results showed that feed restriction had a very significant effect (P<0.01) on feed consumption and FCR but had no significant effect (P>0.05) on protein intake, feed conversion ratio (FCR), growth rate, carcass, and carcass percentage. It can be concluded that treatment D (3-week restriction) showed the best performance with a feed consumption of 903.64 g/head/week, a body weight gain of 170.18/head/week, FCR 5.72, a carcass of 843 g, and a carcass percentage of 57.88%.